OP61 The Future Health and Economic Consequences of Recent Obesity Trends in Ireland. (10th September 2013) - Keaver, L M; Webber, L; Dee, A; Marsh, T; Balanda, K; Perry, I J
Abstract : Background: Given the scale of the current obesity epidemic and its consequences for health there has been increasing concern about the economic burden placed on society in terms of direct healthcare costs and indirect societal costs. In the Republic of Ireland obesity related costs (direct and indirect) have been estimated at 1.13 billion for 2009. The total direct healthcare costs for six major obesity related conditions (coronary heart disease & stroke, cancer, hypertension, type 2 diabetes and knee osteoarthritis) in the same year were estimated at 2.55 billion. The aim of this research is to project disease burden and direct healthcare costs for major obesity related conditions in Ireland to 2030 using the established model developed by the National Heart Forum (UK) for the Foresight: Tackling Obesities project. Methods: Routine data sources were used to derive incidence, prevalence, mortality and survival for coronary heart disease, stroke, cancer, hypertension, type 2 diabetes and knee osteoarthritis as inputs for the model. The model utilises a two stage modelling process to predict future BMI rates, disease prevalence and costs. Stage 1 employs a non-linear multivariate regression model to project BMI trends; stage 2 employs a microsimulation approach to produce longitudinal projections and test the impact of interventions upon future incidence of obesity-related disease. Results: Overweight and obesity are projected to reach levels of 89% and 85% in males and females respectively by 2030. This will result in an increase in the obesity related prevalence of CHD and stroke by 97%, cancers by 61% and type 2 diabetes by 21%. Prevalence of hypertension and knee osteoarthritis is also projected to increase but to a lesser degree. The direct healthcare costs for the six conditions, associated with the projected increase in obesity will amount to €5.4 billion by 2030. A 5% fall in population BMI levels by 2030 is projected to decrease the incidence of CHD & stroke and type 2 diabetes by 35 984 and 37 788 cases respectively, resulting in savings of €495 million in direct healthcare costs. Discussion: These findings have significant implications for policy, highlighting the need for effective strategies to prevent this avoidable health and economic burden. Keywords Foresight; Obesity; Co-morbidities; Burden of disease; Healthcare costs